2020
DOI: 10.3389/fphar.2020.00113
|View full text |Cite
|
Sign up to set email alerts
|

The Regulator of G Protein Signaling Homologous Domain of G Protein-Coupled Receptor Kinase 2 Mediates Short-Term Desensitization of β3-Adrenergic Receptor

Abstract: G protein coupled receptor (GPCR) kinases (GRKs) are key regulators of GPCR signaling. Canonical mechanism of GPCR desensitization involves receptor phosphorylation by GRKs followed by arrestin recruitment and uncoupling from heterotrimeric G protein. Although b3-adrenergic receptor (b3AR) lacks phosphorylation sites by GRKs, agonist treatment proved to induce b3AR desensitization in many cell types. Here we show that GRK2 mediates short-term desensitization of b3AR by a phosphorylation independent mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…In this sense, GRK2 interaction with Gα has been demonstrated by other groups 5,30 and by us (Ref. [6] and Figure 5A).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In this sense, GRK2 interaction with Gα has been demonstrated by other groups 5,30 and by us (Ref. [6] and Figure 5A).…”
Section: Discussionsupporting
confidence: 76%
“…GRK2 is a protein with a confirmed therapeutic potential for several pathologies such as hypertension, heart failure, Alzheimer's, multiple sclerosis, and rheumatoid arthritis. Although its kinase domain has been extensively studied in the search for inhibitors, during the past years its RGS homology domain has also been postulated as an interesting target to be modulated 6,27,32,33,34 . RGS family members have been under study, and several protein inhibitors have been found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations